Relationship Among Building Characteristics, Plant Layout, Landscaping And Student Academic Performance In Kebbi State Secondary Schools, Nigeria - MANGA, Sani Dantani (International Journal of Scientific Research and Management (IJSRM), 2020)
This paper investigated the relationship among building characteristics, plant layout, landscaping and student academic performance in Kebbi State secondary schools, Nigeria. The objectives were to ascertain the characteristics of school plant and if there is any relationship between school plant and student academic performance. The study adopted a descriptive correlational design conducted ex- post facto. Purposive and simple random sampling techniques were used to select 82 boarding schools and 360 teachers out of 1,613. A validated West African Examination Council Results Format; Observation Inventory; and Questionnaire with Cronbach alpha reliability coefficients of 0.83, 0.85 and 0.76 respectively were used to collect data. Rating scales, frequencies, percentages, Analysis of Variance and Multiple Regression analysis at 0.05 alpha level were used in the analysis. It was found that school buildings characteristics, plant layout and landscaping were rated low but were significantly, and highly corelated to student academic performance. It was recommended that school buildings, plant layout and landscaping should be improved to enhance student academic performance